2022
DOI: 10.1002/cam4.4526
|View full text |Cite
|
Sign up to set email alerts
|

Nocardia rubra cell‐wall skeleton influences the development of cervical carcinoma by promoting the antitumor effect of macrophages and dendritic cells

Abstract: Background As an immune enhancer, Nocardia rubra cell‐wall skeleton (Nr‐CWS) has been used to treat persistent human papillomavirus infection and cervical precancerous lesions. However, it is still unclear whether it can be used to treat cervical carcinoma. Methods In our study, the aim was to determine whether Nr‐CWS affects the apoptosis of cervical carcinoma cells by enhancing the antitumor effect of dendritic cells and macrophages in vivo and in vitro. Results The experimental results showed that Nr‐CWS ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Maturation of DCs can be promoted by bacterial components, inflammatory cytokines, or antigen-antibody complexes (36). Nr-CWS is a bacterial-derived extract that activates DCs in vitro (20). In the present study, Nr-CWS enhanced HLA-DR, CD86, and CD83 expression in DCs, increased IL-12 production, and reduced IL-10 production.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Maturation of DCs can be promoted by bacterial components, inflammatory cytokines, or antigen-antibody complexes (36). Nr-CWS is a bacterial-derived extract that activates DCs in vitro (20). In the present study, Nr-CWS enhanced HLA-DR, CD86, and CD83 expression in DCs, increased IL-12 production, and reduced IL-10 production.…”
Section: Discussionsupporting
confidence: 50%
“…Recently, it has been proposed that Nr-CWS facilitates the proliferation and viability of DCs (19). Zhang et al reported that Nr-CWS can promote the maturation of DCs (20). Based on these findings, we explored the response of T cells to DCs stimulated by Nr-CWS.…”
Section: Introductionmentioning
confidence: 95%
“…[25] A study suggests that Nr CWS can promote apoptosis of cervical carcinoma cells by enhancing the antitumor effect of dendritic cells and macrophages. [9] In order to evaluate the effectiveness of 5-ALA PDT for the treatment of cervical LSIL paired with HPV, our study used Nr-CWS as the control group. At 4 to 6 or 12 months of follow-up, our study observed no statistically significant difference in HPV remission between the Nr-CWS group and the 5-ALA PDT group.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Nocardia rubra cell-wall skeleton (Nr-CWS), an immune booster, has been utilized to treat cervical precancerous lesions and persistent HPV infection. [9] A brand-new, minimally invasive treatment method is called photodynamic therapy (PDT). [10] PDT has been recommended as a preferred method for genital warts, skin basal cell carcinoma, and other diseases, but its availability in treating cervical squamous intraepithelial lesion is still unidentified.…”
Section: Introductionmentioning
confidence: 99%
“…The Nocardia rubra cell wall skeleton (Nr-CWS) was extracted from a rubra, a gram-positive bacterium that consists of nocardia acid, arabinogalactan, and mucopolysaccharide. Previous studies have shown that Nr-CWSs can act as an immunomodulator to upregulate the body’s immune function for antitumor purposes, and it can also accelerate the wound repair process in patients with celiac disease [ 1 ]. Some researchers have applied it to mouse skin wounds and found that it can promote healing [ 2 ].…”
Section: Introductionmentioning
confidence: 99%